Letter from P.F. Dujardin & Co. advertising machines and products for metallographic laboratories - P. F. Dujardin & Co. (1910)
P.F. Dujardin & Co. advertises their metallographic devices.
Keywords: Metallography; Scientific apparatus and instruments; P. F. Dujardin & Co.